Final Years of the American Revolution - Wade, Linda R. (Edina, Minnesota ABDO Publishing Company, 2001)
This series tells the story of the struggle for independence.
Keywords: United States - History - Revolution, 1775-1783--Campaigns.; United States - History - Revolution, 1775-1783 -- Peace